Athletic groin pain: a systematic review of surgical diagnoses, investigations and treatment. Issue 19 (6th May 2016) - de SA, Darren; Hölmich, Per; Phillips, Mark; Heaven, Sebastian; Simunovic, Nicole; Philippon, Marc J; Ayeni, Olufemi R
Abstract : Introduction: Athletic groin pain requiring surgery remains a diagnostic and therapeutic challenge. This systematic review aims to identify the most common causes of groin pain in athletes requiring surgery. Additionally, it aims to further characterise their susceptible athlete profiles, common physical examination and imaging techniques, and surgical procedures performed. This will enable the orthopaedic sports medicine clinician/surgeon to best treat these patients. Materials and methods: The electronic databases MEDLINE, PubMed and EMBASE were searched from database inception to 13 August 2014 for studies in the English language that addressed athletic groin pain necessitating surgery. The search was updated on 4 August 2015 to find any articles published after the original search. The studies were systematically screened and data were abstracted in duplicate, with descriptive data presented. Results: A total of 73 articles were included within our study, with data from 4655 patients abstracted. Overall, intra-articular and extra-articular causes of groin pain in athletes requiring surgery were equal. The top five causes for pain were: femoroacetabular impingement (FAI) (32%), athletic pubalgia (24%), adductor-related pathology (12%), inguinal pathology (10%) and labral pathology (5%), with 35% of this labral pathology specifically attributed to FAI. Conclusions: Given the complex anatomy, equal intra-articular and extra-articular contribution, and potential for overlap of clinical entities causing groin pain leading to surgery in athletes, further studies are required to ascertain the finer details regarding specific exam manoeuvres, imaging views and surgical outcomes to best treat this patient population.